Case Report: Opportunities and Challenges of Immunotherapy in Heavily-Treated EGFR-Mutant Advanced Squamous Cell Lung Carcinoma After Progression on EGFR-TKIs and Chemotherapy - Jin, Wei; Wang, Xin; Wang, Jie; Lin, Lin (Frontiers in Oncology, 2022)
Background: Epidermal growth factor receptor (EGFR) mutations have a low incidence in squamous cell lung cancer (SqCLC), and the clinical efficacy of EGFR tyrosine kinase inhibitors (TKIs) in EGFR-mutated SqCLC is far less than that in EGFR-mutated lung adenocarcinoma. The treatment strategy for patients with EGFR-mutated non-small cell lung cancer (NSCLC) who are refractory to EGFR TKIs has become a current dilemma and challenge. Case Presentation: A case of 69-year-old male patient suffering from intermittent cough and haemoptysis was diagnosed with EGFR-mutated advanced SqCLC (stage cT2bN2M1). The patient was treated with camrelizumab alone after five courses of different systemic therapy and achieved partial response,with an eminent progression-free survival of more than 24 months. Grade 1-2 reactive cutaneous capillary endothelial proliferation and mild pruritus were observed during the treatment. No other immune-related adverse events were observed. Conclusion: Monotherapy of immune-checkpoint inhibitors may be considered as a later-line option for EGFR-mutated advanced SqCLC patients with PD-L1 expression.